543 DISSEMINATION AND SAFETY OF ROBOT-ASSISTED ESOPHAGECTOMY IN JAPAN. (14th September 2020) - Nishigori, T; Obama, K; Ichihara, N; Uyama, I; Inomata, M; Watanabe, M; Kakeji, Y; Seto, Y; Miyata, H; Sakai, Y
Abstract: : Robot-assisted surgery for gastrointestinal cancers began to be covered by universal health insurance in April 2018 in Japan. However, the current status of this new procedures such as the number of patients and clinical outcomes was unclear. The aim of this study to retrospectively examine the dissemination and safety of robot-assisted esophagectomy (RAE) in Japan using a nationwide web-based database, or the National Clinical Database (NCD). Methods: The study included patients who underwent RAE or conventional minimum invasive esophagectomy (MIE) and were registered in the NCD in 2018. The outcomes were operative mortality and the numbers of hospitals and surgeons performing the surgeries. Results: The number of patients undergoing RAE and MIE was 122 and 4799, respectively. RAE was performed at 28 hospitals by 37 surgeons, while MIE was done at 523 hospitals by 837 surgeons. In terms of annual case volume per hospital, RAE was likely to be performed in higher volume centers. The number of patients undergoing RAE per month in Japan was less than 5 before insurance coverage began. It has increased to more than 10 since April. Operative mortality occurred in 2 (1.6%) patients following RAE, while it occurred in 78 (1.6%) following MIE. Conclusion: RAE was safely introduced in Japan. The number of patients undergoing RAE and surgeons and hospitals performing it were gradually increasing but still limited.